2006
DOI: 10.1523/jneurosci.0069-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Axon Branch Dynamics by Synaptic Maturation

Abstract: The developmental refinement of topographic projections in the brain is reflected in the dynamic sculpting of axonal arbors that takes place as connections between CNS structures form and mature. To examine the role of synaptogenesis and synaptic maturation in the structural development of axonal projections during the formation of the topographic retinotectal projection, we coexpressed cytosolic fluorescent protein (FP) and FP-tagged synaptophysin (SYP) in small numbers of retinal ganglion cells in living alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
200
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(220 citation statements)
references
References 48 publications
(74 reference statements)
19
200
1
Order By: Relevance
“…Numerous studies have revealed developmentally regulated synaptic maturation during periods when the expression of LTP is also robust (Crair and Malenka, 1995;Rumpel et al, 1998;Chen and Regehr, 2000), and this synaptic maturation is correlated with axon remodeling during map refinement (Meyer and Smith, 2006;Ruthazer et al, 2006). Whether the experimentally induced LTP is physiologically relevant to circuit formation is unclear, however, because of the wide variety of induction protocols used and the lack of information about natural activity patterns during development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have revealed developmentally regulated synaptic maturation during periods when the expression of LTP is also robust (Crair and Malenka, 1995;Rumpel et al, 1998;Chen and Regehr, 2000), and this synaptic maturation is correlated with axon remodeling during map refinement (Meyer and Smith, 2006;Ruthazer et al, 2006). Whether the experimentally induced LTP is physiologically relevant to circuit formation is unclear, however, because of the wide variety of induction protocols used and the lack of information about natural activity patterns during development.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, chronic NMDAR blockade serves to increase RGC arbor branch dynamics, suggesting that NMDAR activity and synaptic maturation normally stabilizes retinotectal projections during circuit formation (Rajan et al, 1999). Recent in vivo imaging of zebrafish and tadpole retinotectal axons reveals that synapse formation and maturation are tightly correlated with branch dynamics and may play an instructive role in arbor remodeling during map formation (Meyer and Smith, 2006;Ruthazer et al, 2006). Indeed, correlated activity is known to regulate RGC axon branch dynamics during development (Ruthazer et al, 2003;Hua et al, 2005), offering additional evidence that the refinement of retinotopic projections proceeds through activitydependent instruction and synaptic competition.…”
Section: Model Of Synaptic-competition-based Retinotopic Map Refinementmentioning
confidence: 99%
“…Images were collected from anesthetized tadpoles (0.02% MS-222; Sigma) positioned under a glass coverslip in a Sylgard chamber. Animal preparation, laser sources, signal amplification, PMT specifications, and YFP/CFP filter sets have been described previously (48). Using the raw image stacks (1-1.5-m z interval), manual reconstructions of the dendritic arbor in three dimensions were generated and then analyzed for total dendritic branch length, branch-tip number, and 3D Sholl analysis (29); radius interval 1 m, averaged over 10-m bins) using Object-Image macros (written by Dr. E. Ruthazer, McGill University, Quebec).…”
Section: Methodsmentioning
confidence: 99%
“…Studies in the retinotectal projection, for example, have shown that branching and synaptogenesis are closely connected and interdependent (Meyer and Smith, 2006;Ruthazer et al, 2006).…”
Section: Ephrina5/trk Interaction In Synaptic Plasticitymentioning
confidence: 99%
“…J. Huang et al, 1999;Alsina et al, 2001;Meyer and Smith, 2006;Ruthazer et al, 2006). Moreover, although there is ample evidence for a role of the EphB subfamily in axonal branching and synaptic plasticity, less is known about that of the EphA subfamily (P. P. W.…”
Section: Ephrina5/trk Interaction In Synaptic Plasticitymentioning
confidence: 99%